Marital quality: parallel between the perspective of couples and measuring instruments - D’Andrea de Andrades, Bruna (2021)
This study aimed to draw a parallel between instruments assessing marital quality and the way couples conceptualize their relationship quality. Twenty-five couples were interviewed to understand their ideas about a good quality relationship. The interviews were analyzed according to the topics couples presented, which were then compared with the concepts included in the instruments measuring marital quality. Five themes were identified, partially correspondent to the concepts assessed by the instruments. Cultural differences were found in the American instruments regarding the valuation of some themes to the detriment of others. Research with the Latin American population is necessary to understand its particularities and to develop measures in accordance with these specificities.